Rapid Determination of Hexane Residues in Refined Vegetable Oils Using Semiconducting Metal Oxide-Based Sensors - Asia Kalinichenko; Benjamin Junker; Udo Weimar; Nicolae Bârsan (Proceedings)
A simple, direct method for the determination residual hexane content in refined oils was developed, which makes use of commercial Semiconducting Metal Oxides (SMOX) sensors and is proposed as an alternative to the currently used standards (ISO 9832:2002, ISO 2719:2016). The main advantages are related to the direct measurement of the headspace of oil samples. The measurements are performed at an oil sample temperature of 30 °C and by spiking the samples with hexane in the 8–132 mg·kg−1 range, which is in line with the requirements of current standard for the maximum residue limit set by European Union regulation. Using separate measurements performed with the help of a computer-controlled gas mixing system it is possible to determine the relationship between the concentration of hexane in oil and in the headspace.